Physicomechanical characterization and biological evaluation of bulk-fill composite resin - Armiliana Soares NASCIMENTO; Daniel Bezerra LIMA; Marcus Vinicius Lia FOOK; Monica Soares de ALBUQUERQUE; Eliane Alves de LIMA; Marcos Antonio SABINO; Silvia Maria Pinto BORGES; Pedro Tardelly Diniz FILGUEIRA; Yasmine Carvalho de SOUSA; Rodivan BRAZ (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to evaluate the cytotoxic effect, degree of conversion (% DC), Vickers hardness (VH), and surface morphology of composite resins. Eleven resins, nine bulk-fill resins, and two conventional resins were evaluated. Each material was sampled to evaluate DC (using FTIR), VH, cytotoxicity (using MTT and Neutral Red - NR test), surface morphology (using SEM and AFM), and organic filler (using EDS). All statistical tests were performed with SPSS and the level of significance was set at 0.05. MTT revealed that the materials presented low or no cytotoxic potential in relation to the control. Opus was the resin with the lowest cell viability at a 1:2 concentration at 72 h (32%) and at 7 days (43%), but that significantly increased when the NR test was applied at a 1:2 concentration after 7 days. Thickness and surface subjected to polymerization had no influence on DC, and differences were observed only between the materials. In the microhardness test, statistical differences were observed between the evaluated thicknesses. The bulk-fill resins analyzed in this study exhibited low and/or no cytotoxicity to L929 cells, except for Opus, which showed moderate cytotoxicity according to the MTT assay. When the NR test was used, results were not satisfactory for all composites, indicating the need for different methodologies to evaluate the properties of these materials. The assessed resins demonstrated acceptable physicomechanical properties.